Evaluation of novel composition (SiO2-CaO-Na2O-P2O5, SrO-CuO) degradable amorphous silicate glasses properties and comprehensive characterization of the thermal features - Ozarslan, Ali Can; Yucel, Sevil (ELSEVIER SCI LTD, 2023)
The current work presents and discusses the findings of a comprehensive study on the structural, chemical and thermal properties of SrO and CuO incorporated SiO2-CaO-Na2O-P2O5 amorphous silicate glass with a novel composition. Here, fundamental features (experimental density, oxygen density, and hardness) of all glasses were determined and chemical as well as phase composition of the glasses was verified with XRF and XRD, respec-tively. Moreover, the thermal behavior (viscos flow and crystallization kinetics) of amorphous silicate glass was investigated by non-isothermal methods using DTA analysis. The activation energies of glass transition (Eg) were calculated in the range of 546-1115 kJ/mol by Kissinger method, whereas the activation energies of crystalli-zation (Ec) were calculated in the range of 164-270 kJ/mol by three different methods (Kissinger, Ozawa, Yinnon and Uhlmann). Avrami exponent (n) values ranged from 1.17 to 3.28 demonstrated that amorphous silicate glasses have different crystallization mechanism. Working temperature, which is one of the parameters indi-cating glass stability, increased with the incorporation of Sr and Cu from 187 degrees C to 245 degrees C. The initial dissolution measurement has been applied to study the degradability behavior of Sr and Cu incorporated amorphous glasses in vitro. Quantitative evaluation of Si4+ (0.156-0.373 kV), Ca2+ (0.043-0.332 kV), Na+ (0.044-0.329 kV), P5+ (0.057-0.289 kV), Sr2+ (0.134-0.385 kV), and Cu2+ (0.090-0.203 kV) depending on the ion activation energy (Ea-ion) and ion concentration at different temperature values (24, 37 and 55 degrees C) was performed in contact with Tris-HCl solution by ICP-OES analysis. The results revealed that investigated glasses were degradable and incorporation of Sr and Cu affected the glass initial dissolution. Overall, investigated glasses are suitable for various application such as hot-working production, glass-ceramic manufacturing, and glass or glass-ceramic scaffolds fabrication, due to wide working temperature ranges and high crystallization tendencies of the developed glasses.
Keywords: Amorphous silicate glass; Degradability behavior; Incorporation of strontium and copper; Thermal behavior; IN-VITRO BIOACTIVITY; BONE TISSUE; CRYSTALLIZATION BEHAVIOR; MECHANICAL-PROPERTIES; STRONTIUM; 45S5; COPPER; DISSOLUTION; SUBSTITUTION; SCAFFOLDS; Materials Science